SOSIALISASI PENGGUNAAN MEDIA SOSIAL DAN INTERNET YANG AMAN UNTUK GURU SMK NEGERI 1 LHOKSEUMAWE - munirul ula; Rizal Tjut Adek; Muhammad Muhammad; Mukhlis Mukhlis; Muhammad Fauzan; Bustami Bustami (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
Social media does provide a plethora of fun perks. However, social media and the internet also bring negative impacts and new dangers. Technology of internet can result in many negative things in society when it is not accompanied by knowledge of wise internet use. In this era of globalization, the internet has become a major need in everyday life. The internet has a very good role in helping the role of business, learning, communication and other problems that are found when not using the internet or commonly called the manual method. Not using and following the development of the internet, can lead to lagging business and economic aspects. The method used in this service is direct presentation and workshop. The purpose of the training is to raise awareness about the possible dangers of using social media. The materials presented in this training include cases of fraud through social media, cases of identity theft and others. After that, preventive measures against the threats that may be faced and how to use social media properly are conveyed in this socialization. This training and socialization is very useful to raise awareness of teachers about the dangers that may arise in the use of the internet and social media, so that this knowledge can be conveyed and taught to students at SMK Negeri 1 Lhokseumawe and also the surrounding environment. Key Words: Awareness of social media, healthy and safe Internet, SMK teacher socialization